(untitled) (Indian Journal of Arid Horticulture, 2025)
Guava, the "apple of tropics" or "poor man’s apple" is a popular and common fruit which belongs to the family Myrtaceae. It is grown practically in most of the states of India and excels in productivity, hardiness, adaptability and nutritive value. The fruit is a rich source of vitamin-C i.e. 234.3 mg/100g. Physical characters such as fruit weight, volume, specific gravity and dry matter content are influenced positively by their position on the tree in different directions i.e. east, west, north and south. These directions are mainly concerned with exposure of tree canopies to the light periods. The fruits from winter season crop develop more uniform colour with good quality and store better than rainy season crop, Tiwari et al. (2005). The disappearance of the green pigment is considered as a criteria in judging the harvest maturity.